Hsa_circ_0006837 suppresses gastric cancer cell proliferation, migration, and invasion via the modulation of miR-424-5p - Yanxin He; Yeyu Sun; Yinglan Zheng; Yanfang Jiang; Na Li; Wenjie Zhao; Wanhua Ren (Hereditas)
Abstract Background The mechanism by which circRERE (hsa_circ_0006837) modulates the malignant progression of gastric cancer was investigated to identify a novel biomarker and therapeutic target for this disease. Methods Hsa_circ_0006837 expression in GC tissues and cells was detected by RT-qPCR. Several data analysis methods were used to evaluate the significance of dysregulated hsa_circ_0006837 in GC. The patients were followed up for five years, and survival analysis was conducted using Kaplan-Meier curves. Cox regression was subsequently performed to analyze the risk factors for prognosis. The malignant behaviors of the cells were detected by the CCK-8 and Transwell assays. The relationship between hsa_circ_0006837 and miR-424-5p was assessed by conducting Spearman correlation analysis and verified by dual-luciferase reporter assay. Results Hsa_circ_0006837 expression decreased in patients with GC, indicating a poorer patient prognosis. In GC cells, hsa_circ_0006837 overexpression suppressed malignant behaviors. Mechanistically, miR-424-5p was identified as a target of hsa_circ_0006837. The overexpression of miR-424-5p partially counteracted the suppressive effects of upregulated hsa_circ_0006837 on the malignant behaviors of GC cells. FBXO21 was identified as a downstream gene of the hsa_circ_0006837/miR-424-5p axis. Conclusions To summarize, hsa_circ_0006837 is a biomarker for the prognosis of GC. Mechanistically, hsa_circ_0006837 overexpression can modulate the malignant behaviors of GC cells through miR-424-5p.